Behavioral intentions to stop consuming risky foods related to degenerative diseases among Indonesian university students: a descriptive study - Sitti Nur Djannah; Lina Handayani; Intan Wahyuni Tukiyo; Trinur Afika Mandar (International Journal of Public Health Science (IJPHS), 2026)
Food consumption habits nowadays are diverse, particularly the many choices of processed and quick food at low prices, which, including among students, are unhealthy and unsafe, with unbalanced nutritional levels that can cause a variety of degenerative diseases. This study aimed to describe students' intentions to stop consuming risky foods, grounded in the theory of planned behaviour (TPB). This study is a quantitative descriptive study conducted with second- and fourth-semester students in the public health study program. The sample was selected using accidental sampling, resulting in 87 students participating in the questionnaire. The data were analyzed descriptively and presented in tables and narratives. The study shows that fatty meat/offal, canned foods, pickled foods, and dried sweets are consumed frequently. The non-intentional group comprised processed cheese, frozen sweets and ice cream, quick noodles, and fried foods. Among 10 dangerous foods, fried foods, processed cheese, pickles, and frozen desserts are the least likely to be substituted. Most responders were unsure of the quitting time. Students did not plan to quit unhealthy foods. Students did not have a firm intention to stop consuming hazardous foods such as processed cheese, frozen sweets, instant noodles, and fried foods.